2018
DOI: 10.15446/rsap.v20n2.50676
|View full text |Cite
|
Sign up to set email alerts
|

Factores psicológicos predictores de estilos* de vida saludable

Abstract: Objetivo Presentar un modelo estadístico robusto que considere algunos factores psicológicos como predictores del estilo de vida saludable.Materiales y Métodos Se aplicó una batería compuesta por instrumentos validados para evaluar creencias y prácticas saludables, estilos de afrontamiento, salud mental positiva y autoeficacia percibida en una muestra de 570 estudiantes universitarios de Bogotá, Colombia. Con la información obtenida se desarrollaron análisis descriptivos, de varianza y correlacionales, así com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
(26 reference statements)
0
4
0
8
Order By: Relevance
“…Although the objective of this study was not to directly evaluate the work related to the interaction between ER processes and BEB behaviors, the reflection on the findings does allow generating new investigations in which ER is manipulated and the effect size is contrasted for the increase of health self-care behaviors (Gómez-Acosta, 2017). This may enable the provision of evidence regarding the ER relationship, the increase in BEB behaviors and adherence to treatment/ reduction of health situations such as morbid obesity, eating disorders, cardiovascular diseases, diabetes mellitus, insomnia and other chronic non-communicable diseases (Gómez-Acosta, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the objective of this study was not to directly evaluate the work related to the interaction between ER processes and BEB behaviors, the reflection on the findings does allow generating new investigations in which ER is manipulated and the effect size is contrasted for the increase of health self-care behaviors (Gómez-Acosta, 2017). This may enable the provision of evidence regarding the ER relationship, the increase in BEB behaviors and adherence to treatment/ reduction of health situations such as morbid obesity, eating disorders, cardiovascular diseases, diabetes mellitus, insomnia and other chronic non-communicable diseases (Gómez-Acosta, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It can be concluded that, in effect, ER has an impact on the physical health of people, and is not only directly linked to the processes of psycho-neuro-endocrine-immune homeostasis and associated epigenetic correlates, but can also indirectly affect this balance through the interaction that RE holds with the behaviors associated with BEB. In this case, it is convenient to develop more research that will allow, on the one hand, have a better understanding of the reciprocal functioning of these systems and their spiraling feedback, and on the other hand, that will lead to a better understanding of the relationships between ER and other psychological factors underlying health protective practices (Ellis et al, 2019;Gómez-Acosta, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…En el caso de Latinoamérica, se ha comprobado una relación significativa entre el desarrollo de las Habilidades Sociales, el logro académico de las y los estudiantes, sus cualidades y sus estilos de vida (Gómez-Acosta, 2018;Quiñones, 2020). Al respecto, se ha comprobado que existe dependencia entre la conducta disruptiva y las habilidades sociales (Colichón, 2020).…”
Section: Estado De La Cuestiónunclassified
“…Concretamente, el estado físico en un estudiante puede entenderse como las condiciones físicas personales, en cuanto a la situación de su organismo, que le permitan un buen rendimiento en el estudio (3) . Respecto al estado físico, puede afirmarse que es una variable comúnmente asociada a aspectos relativos a la salud como la calidad de vida y a mejores hábitos alimentarios (4) ; y de manera similar, el estado físico está asociado con otras variables de carácter psicológico como el afrontamiento, la satisfacción general, las habilidades interpersonales y la autoeficacia (5) .…”
Section: Introductionunclassified